Dynamiczny charakter zmiennych indywidualnych – wyzwania badawcze i implikacje dydaktyczne - Pawlak, Mirosław (Neofilolog, 2017)
Not so long ago individual difference factors were perceived as relatively stable attributes of learners and it appeared that their impact on the outcomes of the language learning process could be determined in a straightforward manner. There was a widespread belief that it was sufficient to design appropriate data collection instruments, carefully validate them, collect the requisite data concerning the variable in question as well as learners’ attainment, and then apply the procedures of inferential statistics in order to arrive at conclusions in this respect (Dörnyei, 2005). Such findings could later be used as a point of reference for pedagogical implications for teachers. However, the findings of research conducted over the last decade, in particular such that has focused upon motivation and willingness to communicate (e.g., Dörnyei, MacIntyre and Henry, 2015), have clearly demonstrated that the situation is much more complicated, because such factors are subject to constant fluctuations, both over longer periods of time, sequences of classes, single lessons or even specific tasks implemented by teachers. This phenomenon brings with it a number of challenges, not only with respect to designing and conducting empirical studies but also in regard to the steps that should be taken to take account of learners’ individual profiles. The main aim of the present paper is to demonstrate how the dynamic nature of individual difference factors can be accommodated in empirical research as well as elucidating its consequences for the individualization of the process of language learning in the classroom and beyond.